Analysis of the Role of Savings and Loan Cooperatives in the Development of Micro, Small, and Medium Enterprises in Jati Village - Rismawan, Diki; Kusmayadi, Dicki (Universitas Muhammadiyah Makassar, 2025)
Cooperatives play an important role in strengthening the economic foundation, especially for Micro, Small and Medium Enterprises (MSMEs). This is done through providing adequate liquidity to support lending activities to cooperative members who act as MSME actors. Given the importance of MSMEs in economic progress, the government needs to continue to encourage and develop this economy with full support. One important aspect is easy access to capital and marketing assistance. The role of financial institutions, especially banks, is very important in providing access to credit to MSME players, which have great potential in the economy. Because with easy access to capital loans, MSME players can develop the quality of their business. This type of research is descriptive qualitative with data collection techniques, namely interviews, observation, and documentation, with informants as many as 6 MSME actors using a purposive sampling formula from a total of 62 MSME actors. The results of this study indicate that capital is an important element in running a business. With sufficient or large capital, entrepreneurs can develop their business more widely. The existence of capital assistance from cooperatives has a good impact because with this, MSMEs are able to increase the development of MSMEs in the teak village area. The results obtained, there are 90% of MSMEs experiencing an increase in terms of business scope and turnover obtained.